An empirical study of the relationships of investment tax incentives and corporate governance on real corporate investment in the Malaysian manufacturing sector / Mohamad Faizuddin Alimon - Mohamad Faizuddin , Alimon (2022)
Investment tax incentives have been employed extensively to stimulate real investment in the Malaysian manufacturing sector. Real investment is crucial for creating new job opportunity, lowering the cost of capital, enlarging profit appropriation margin and shortening the pay-back period, as well as generating future tax revenue for government socio-economic development. However, ineffective investment tax incentives can be detrimental to a country’s revenue system. CCorporate governance, which shares the goal of maximizing profits with investment tax incentives, serves as a mechanism to safeguard the interests of parties involved in a company’s investment through institutional process. Most literature supports the effectiveness of investment tax incentives in promoting real investment, which is consistent with the widespread adoption of such incentives by developed and developing coutries. Additionally, literature on corporate governance emphasizes its crucial role in successful investment. This study unravels reservations on the investment tax incentives and real investment positive relationship with corporate governance moderations over the period of 2001 to 2015. During the incentive period of 2001 to 2005, Investment Tax Incentives, as well as specifically Pioneer Status (PS), Investment Tax Allowance (ITA) and Reinvestment Allowance (RA) had positive relationships with Real Investment, while Corporate Governance interactions had varying positive or negative relationships. However, reservations emerge in the post-incentive period of 2006 to 2015, in which Investment Tax Incentives had a negative relationships with Real Investment, and the Corporate Governance interactions had negative relationships. This is further supported by consistent negative relationships between Corporate Governance interactions and Real Investment, despite positive relationships between specific investment tax incentives of PS and RA and real investment, and a negative relationship between ITA and real investment. This highlightss the limited effectiveness of investment tax incentives to stimulate real investment. The lack of corporate governance connections on investment tax incentives role in real investment establishment in the post-incentive period may explain this scenario. Moreover, absence of periodical assessment of investment tax incentives programs and the isolation of the corporate governance in the establishment of real investment may also contribute to thisunfavourable situation. Therefore, the study strongly recommends recognizing the importance of corporate governance as an integral part of investment tax incentives and real investment establishment.